Student Centered Learning In Surah Thaha 17-18 And It's Implication In Islamic Boarding School Education - Auliyah, Khusnul; Suwarno, Suwarno; Chasanah, Uswatun; Ali, Ramsah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Qur'an as a guide for humans has provided a complete guide to life, one of which is a guide in education. Of the many verses of the Qur'an that discuss education, the author is interested in studying the learning methods of active learners in the perspective of the Qur'an Surah Thaha verses 17-18, with a focus on the problem of the concept of student-centered learning in the content of Surah Thaha verse 17. -18, and its implications in pesantren education. This research is library research, to build a concept or theory that becomes the basis of study in research. The data used in this study is qualitative in the form of concepts, theories, and formulations that are relevant to the research made. The data analysis used is content analysis and descriptive analysis. Content analysis was used to analyze the messages contained in the Al Quran Surah Thaha verses 17-18 related to learning, while descriptive analysis was used to collect and write down data related to student-centered learning in the perspective of Al Quran Surah Thaha verses 17-18 and implications for education in boarding school. The results of the research on the content of the letter thaha verse 17 in the learning process educators must invite students to think critically in solving a problem to gain knowledge, while the content of the letter thaha verse 18 shows that as educators must be able to appreciate the findings of students in gaining knowledge, but students should not bring themselves to be arrogant. And the implications of Islamic boarding school education are reflected in the teaching methods of Islamic boarding schools that require students or students to develop their potential.Â